Programma: 2 december Radiohead; 3 december Test Department; 4 december Beck; 5 december The Big Awakening; 6 december Pato Banton & The Reggae Revolution
Programma: 2 december Radiohead; 3 december Test Department; 4 december Beck; 5 december The Big Awakening; 6 december Pato Banton & The Reggae Revolution.